The endurance effort on a mechanical treadmill does not activate the complement system among trained young women - Robert Nowak; Patrizia Proia; Dorota Kostrzewa-Nowak (PLoS ONE, 2026)
The complement system (CS) plays a crucial role not only in pathogen-related immune responses but also in immunomodulatory effects associated with increased levels of damage-associated molecular patterns and tissue regeneration. The involvement of CS in response to physical exertion remains unclear. In the present study, the impact of an endurance effort on a mechanical treadmill on CS activation was investigated in healthy young premenopausal women. Twenty-eight well-trained women aged 21–26 years, playing handball or soccer, respectively, performed a progressive test on a mechanical treadmill until exhaustion. The CS component (C1q, C2, C3, C3b/iC3b, C4, C4b, C5, C5a, Factors I, H, B, adipsin, and mannose-binding lectin) concentration in blood was analyzed before, after the test, and 24 hours after the physical test using Luminex xMAP (Multi Analyte Profiling) technology. Progressive effort did not significantly affect the analyzed CS compounds. The lack of CS activation observed in the studied groups of young women suggests that the endurance effort on a mechanical treadmill did not activate an innate immunity. From this perspective, it does not appear to be an inflammatory factor. Considering the small number of participants, this hypothesis needs further exploration.